Gut as the target tissue of mercury and the extraintestinal effects. (15th January 2023) - Tian, Xue; Lin, Xiaoying; Zhao, Jiating; Cui, Liwei; Gao, Yuxi; Yu, Yong-Liang; Li, Bai; Li, Yu-Feng
Abstract: Mercury (Hg) is harmful to the environment and human health. The gut plays important roles as the biological, chemical, mechanical, and immune barriers in animals and human beings. It has been known that Hg can be absorbed and methylated/demethylated in the gut, on the other hand, the impacts of Hg to the gut (especially the gut microbiota) is less studied. This review paper summarizes the impacts of inorganic Hg (IHg) and methyl Hg (MeHg) on gut barriers and the extraintestinal effects (damage to other organs such as the liver and brain). Both IHg and MeHg were found to cause intestinal microbial disorders, abnormal metabolites production, tight junction damage, and immune responses in the gut. The damage to the gut also contributed to the extraintestinal effects like the hepatotoxicity by IHg and the neurotoxicity by MeHg. In all, it is proposed that the gut should be considered as an important target tissue of Hg exposure, and the regulation of gut microbiota may have the potential for the prevention and control of the toxicity of Hg. Graphical Abstract: ga1